Cardio-Respiratory Endurance Responses Following a Simulated 3 × 3 Minutes Amateur Boxing Contest in Elite Level Boxers - El-Ashker, Said (Sports (Basel), 2018)
This study aimed at examining physiological responses (i.e., oxygen uptake [VO(2)] and heart rate [HR]) to a semi-contact 3 × 3-min format, amateur boxing combat simulation in elite level male boxers. Eleven boxers aged 21.4 ± 2.1 years (body height 173.4 ± 3.7, body mass 74.9 ± 8.6 kg, body fat 12.1 ± 1.9, training experience 5.7 ± 1.3 years) volunteered to participate in this study. They performed a maximal graded aerobic test on a motor-driven treadmill to determine maximum oxygen uptake (VO(2max)), oxygen uptake (VO(2AT)) and heart rate (HR(AT)) at the anaerobic threshold, and maximal heart rate (HR(max)). Additionally, VO(2) and peak HR (HR(peak)) were recorded following each boxing round. Results showed no significant differences between VO(2max) values derived from the treadmill running test and VO(2) outcomes of the simulated boxing contest (p > 0.05, d = 0.02 to 0.39). However, HR(max) and HR(peak) recorded from the treadmill running test and the simulated amateur boxing contest, respectively, displayed significant differences regardless of the boxing round (p < 0.01, d = 1.60 to 3.00). In terms of VO(2) outcomes during the simulated contest, no significant between-round differences were observed (p = 0.19, d = 0.17 to 0.73). Irrespective of the boxing round, the recorded VO(2) was >90% of the VO(2max). Likewise, HR(peak) observed across the three boxing rounds were ≥90% of the HR(max). In summary, the simulated 3 × 3-min amateur boxing contest is highly demanding from a physiological standpoint. Thus, coaches are advised to systematically monitor internal training load for instance through rating of perceived exertion to optimize training-related adaptations and to prevent boxers from overreaching and/or overtraining.